Teacher education for inclusion: Can a virtual learning object help? - Alquati Bisol, Cláudia; Valentini, Carla Beatris; Rech Braun, Karen Cristina (Computers and education, 2015)
Inclusive education has occupied a central role in educational planning especially over the last two decades of the 20th century. This article presents an evaluation of the virtual learning object (LO) Incluir—a digital resource designed to support learning. It was created to work as a complementary tool for teacher education that aimed at promoting reflection on inclusion and resignification of teachers' practice. We present some aspects of inclusive education in Brazil and our perspective on teacher education for inclusion. Then we explore the learning object, the pedagogical framework that guided its conception, and the survey that we conducted designed to evaluate the object in its technical and pedagogical aspects. A total of 163 participants answered a questionnaire comprised of 20 closed questions and 3 open-ended questions. Simple descriptive statistics allowed us to determine that participants rated the object very positively. Thematic content analysis was used to organize the qualitative data of the two open-ended questions in three analytical categories. Simple quantification and description was used to analyze the third open-ended question. We concluded that the LO is a valuable complementary resource that contributes to teacher education for inclusion. •We developed a virtual learning object for teacher education for inclusion.•We conducted a survey designed to evaluate the learning object.•The learning object has proven to be useful to promote reflection on inclusion.•The learning object has potential to facilitate resignification of teachers' practice.